STUDENTS’ ABILITY TO IDENTIFY PROMINENCE PLACEMENT IN AUDIOBOOK - Sari, Dian Ratna; Susilawati, Endang; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to describe English Language Study Program students? ability in identifying prominence placement in audiobook. The subject of the research was Semester 5 students of English Language Education Study Program Teacher Training and Education Faculty Tanjungpura University Pontianak in academic year 2016/2017 that had taken requisite subjects related to English listening subjects. The researcher conducted a descriptive research on students? level of ability in identifying prominence placement in audiobook. A listening test to identify three circumstances governing prominence placement (which are New Information, Emphatic Stress, and Contrastive Stress) and an interview were conducted as activities of data collecting. The research findings showed that on average, the students were at very poor level in identifying prominence placement in audiobook with the average score of 49.09. Narrowing down to the ability to identify each circumstance governing prominence placement, the students were found to be on very poor level of identifying New Information circumstance. They were found to be on poor level of identifying Emphatic Stress circumstance. For identifying Contrastive Stress circumstance, they were also found to be on poor level. Based on the supporting data, it was assumed that the students? level of ability in identifying prominence placement in audiobook was influenced by their unfamiliarity with prominence and their lack of practice in identifying prominence. Keywords: Students? Ability, Identify, Prominence Placement, Audiobook